The Effectiveness of Touch / Don’t Touch Technique to Improving the Understanding of Sexual Abuse Prevention for Primary School Students Number 060885 in Medan City - Nasrun, Nasrun; Nasution, Nani Barorah (Universitas Negeri Semarang, 2016)
There are currently efforts to resolve cases of child sexual abuse in Indonesia by manage legally laws that provides penalties for those who engage in child sexual abuse cases. However it is still less attention in the education field, educational institutions have not been able to play an active role and become a shield to prevent child sexual abuse. In other words, it should be emphasized that prevention efforts have to be comprehensive, which is mean that not only done by one party (parents or relatives) only, but must be integrated with the government, community organizations, schools, professionals, who does have a concentration on growth and child development. In Indonesia, the Indonesian Child Protection Commission (KPAI) admits received many complaints of violence and sexual abuse of children, based on KPAI data that has been collected in the period January to March 2014. During those three months, there were 379 cases reported to the KPAI, one of which is sexual violence that afflicts kindergarten students at the Jakarta International School (JIS). Based on the data described above is carried out preventive measures to prevent the occurrence of child sexual abuse in the form of education and research. The research conducted by the author with the title